Desenvolvimento e avaliação experimental de uma mistura de diesel, etanol anidro e um bioaditivo cossolvente renovável - Cristófoli, Julio Barreto (2018)
The need to reduce undesirable emission and the seek for better performance in motors came to increase the interest of researchers for biofuels, especially the ones that are from renewable sources. This study aimed at developing and experimentally evaluating a diesel and ethanol mixture by inserting a commercial co-solvent bio additive, determining the physical-chemical characteristics of this alternative biofuel and comparing the combustion parameters in relation to S500 diesel. The proposed mixture was 50% diesel S500, 30% anhydrous ethanol and 20% commercial co-solvent bio additive. The theoretical simulation of combustion properties based on the analyzed fuel elementary composition was conducted with the commercial software Industrial Combustion Acomb 5, version 5.21. The ternary mixture was submitted to trials following the current legislation on A and B diesel S500 as described by the ABNT and ASTM technical regulations. The studied alternative biofuel showed eleven parameters within the ones stipulated by the ANP n. 50 and six which need alterations. The parameters which showed results according to the ANP n. 50 resolutions were: calorific power, aspect and color, total sulfur, distillation, specific mass, cinematic viscosity, clogging point, ashes, total contamination, water and sediments and lubricity. Other parameters did not adequate to said resolution, standing out among them the flash point, derived cetane number, carbon micro residue, water content by Karl Fisher, oxidative stability and the acidity level. Thus, alterations such as cetane promoters and natural or synthetic antioxidants addition, among others, are needed to reach full adequacy of its combustion parameters to the current legislation